Sports - politics relationship in Turkey in the early years of the republic - Ayhan Dever; Burkay Cevahırcıoglu; Bahadır Demır (Selcuk University, 2017)
One of the most significant of shortcomings in the field of sports in Turkey is that the History of Sports in Turkey is not preserved in its well-deserved place. Although some research is being carried out by utilizing the limited resources available, obviously no new data is discovered in this area. In fact, the information accumulated via the oral narrative tradition till this day has lost its validity for some reasons along the way; consequently, alternative versions of the History of Sports in Turkey have evolved thus emerged. In order to avoid such complications, this study seeks to reach out to firsthand information and complements its data with references from the newspapers and magazines of the early-republican era. The study aims at revealing information about the Federation of Turkish Training Associations (TİCİ, 1922-1936), the Turkish Sports Association (TSK, 1936-1938) and the General Directorate for Physical Education (BTGM, 1938-1983), which were established at various phases of the Early Republican Era and in charge of the administration of sports. The study also aims at indicating the relationship of these administrative bodies with the politics and making conclusions by comparison. Leastwise, the study aims at making some contribution to the History of Sports in Turkey particularly by means of firsthand resources and revealing unknown political arguments.